Performance Study of a Novel Dual Rotor Sandwich Stator Fusion Magnetic Pole Six-Phase Permanent Magnet Synchronous Generator for Geothermal Energy Extraction - Kumar R.R.; Paul R.; Sarma J.; Kumari A.; Chetri C.; Saket R.K.; Padmanaban S.; Leonowicz Z. (My University, 2025)
The salient features of a Novel Dual Rotor Sandwich Stator Fusion Magnetic Pole Six Phase Permanent Magnet Synchronous Generator (NDRSSFMPSP-PMSG) for Geothermal Energy Extraction have been highlighted in the research paper. The energy retained inside the outer layer of the earth which is then transported to the surface by steam or liquids is commonly referred to as geothermal power. In Geothermal Power Plants (GPPs), synchronous generators are commonly installed. However, it seems that using a multi-phase PMSG to produce electricity from accumulated geothermal heat energy is a better alternative. The multiphase system outshines the conventional three-phase system in terms of power density, efficiency, finer torque quality, compact design, and reliability. The novelty of the machine lies in the utilization of a fusion magnetic pole which is a combination of surface mounted and hybrid delta shaped magnet. Further the use of a dual rotor-stator topology improves the power density of the machine. The Finite Element Method (FEM) is used to quantify machine parameters including the induced Electromotive Force (EMF), output strength, efficiency, total harmonic distortion (THD), and voltage regulation for the proposed generator. The analysis of the above parameters reveals that the suggested generator outperforms conventional synchronous generators and is best suited for GPPs. © 2021 IEEE